19F MRI Nanotheranostics for Cancer Management: Progress and Prospects. (12th January 2022) - Li, Yanan; Cui, Jing; Li, Chenlong; Zhou, Huimin; Chang, Jun; Aras, Omer; An, Feifei
Abstract: Fluorine magnetic resonance imaging ( 19 F MRI) is a promising imaging technique for cancer diagnosis because of its excellent soft tissue resolution and deep tissue penetration, as well as the inherent high natural abundance, almost no endogenous interference, quantitative analysis, and wide chemical shift range of the 19 F nucleus. In recent years, scientists have synthesized various 19 F MRI contrast agents. By further integrating a wide variety of nanomaterials and cutting‐edge construction strategies, magnetically equivalent 19 F atoms are super‐loaded and maintain satisfactory relaxation efficiency to obtain high‐intensity 19 F MRI signals. In this review, the nuclear magnetic resonance principle underlying 19 F MRI is first described. Then, the construction and performance of various fluorinated contrast agents are summarized. Finally, challenges and future prospects regarding the clinical translation of 19 F MRI nanoprobes are considered. This review will provide strategic guidance and panoramic expectations for designing new cancer theranostic regimens and realizing their clinical translation. Abstract : The unparalleled molecular superiority of fluorine‐19 endows it with powerful non‐invasive and zero‐interference quantitative magnetic resonance imaging (MRI) performance. The stunning advancement of nanoarchitecture technology strengthens the significance of fluorinated nanoprobes in the precise theranostics of cancer. Overcoming obstacles associated with nanoplatform optimization and mechanism exploration will inspire 19 F MRI to open unprecedented prospects for personalized cancer management.